Implantable devices, Nano-, and Micro-capsules for the Next Generation of targeted Nanomedicine and Life Sciences Nano-tools - Gomez Palacios, Luna R. (2023)
In this communication the concept of functional materials is understood such as real modified substrates for nanomedicine applications. Functional and modified substrates focused on microcapsules and devices for new nanomedicine diagnosis and treatments. Cases of different materials are shown to support the functionality strategy, as in particular chemicals, pharmacophores, and controlled nano-chemistry for the design of nanoplatforms. Recent studies have reported hybrid inorganic/organic compositions for biocompatible, biodegradable, and support materials added to particular physical properties such as conductive, semiconductive, and high electromagnetic fields from the near field within the nanoscale to far-field applications and new nano-pharmacophores and nanomedicine therapeutics. New approaches are shown from the nano-scale to the micro- and higher sizes of substrates for improved therapeutic strategies. Micro-capsules for biosensing and drug delivery applications were developed. In addition, we report recent and novel research centered on implantable, portable, and wearable devices applied to future treatments.